2021
DOI: 10.1111/scs.12991
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as a tool to reduce nausea in terminally ill patients

Abstract: Trial registration: The full trial protocol is available at ClinicalTrials.Gov . The study has been registered at this international database retrospectively, but it has been registered prospectively in a national database, and no changes to the study have been made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The USA National Comprehensive Cancer Network (NCCN) guidelines listed acupuncture as one of the alternative methods that can be used as a supplementation treatment when a patient experiences neuropathic pain, arthralgia or myalgia [99,[113][114][115]. The Society for Integrative Oncology in ASCO Guidelines recommends (moderate strength of the recommendation) acupuncture to patients suffering from joint pain after aromatase-inhibitor therapy in breast cancer survivors; general pain or musculoskeletal pain caused by cancer; and pain during systemic cancer therapy.…”
Section: Acupuncturementioning
confidence: 99%
“…The USA National Comprehensive Cancer Network (NCCN) guidelines listed acupuncture as one of the alternative methods that can be used as a supplementation treatment when a patient experiences neuropathic pain, arthralgia or myalgia [99,[113][114][115]. The Society for Integrative Oncology in ASCO Guidelines recommends (moderate strength of the recommendation) acupuncture to patients suffering from joint pain after aromatase-inhibitor therapy in breast cancer survivors; general pain or musculoskeletal pain caused by cancer; and pain during systemic cancer therapy.…”
Section: Acupuncturementioning
confidence: 99%
“…Several randomized, multicenter studies have shown that AC can be used as a supportive antiemetic in pediatric cancer patients receiving chemotherapy to reduce the use of antiemetic medications 156,157 . Several clinical trials have shown that AC can reduce the severity of chemotherapy‐induced nausea and vomiting, 43–46,158 as well as mitigate the adverse effects of antiemetic drugs 47–49 . However, it has a relatively minor role in preventing its occurrence 50 .…”
Section: Clinical Applications Of Acupuncture In Cancer Therapymentioning
confidence: 99%